The impact of family farming on Afrotropical flower fly communities (Diptera, Syrphidae): A case study in Tanzania - Sija Kabota; Jacqueline Bakengesa; Jenipher Tairo; Abdul Kudra; Ramadhani Majubwa; Marc De Meyer; Maulid Mwatawala; Kurt Jordaens; Massimiliano Virgilio (PLoS ONE, 2025)
To provide empirical evidence about the impact of family farming on Afrotropical flower fly communities (Diptera, Syrphidae), we established a large experimental setup in the Morogoro area (Eastern Central Tanzania) and quantified insect abundance and diversity in contrasting agricultural landscapes. Over the two years of this study, we collected 12,969 flower flies from 55 species and 3 subfamilies: Eristalinae (29 species), Microdontinae (2 species), and Syrphinae (24 species). The ten most abundant species contributed to 84.95% of specimens. Overall, we did not observe major changes in species richness or diversity between agroecological and conventional farming. In contrast, higher abundances of the two dominant species, Toxomerus floralis (Fabricius, 1798) and Paragus borbonicus Macquart, 1842 (69.49% of all specimens collected) were observed in agroecological treatments. This effect was more pronounced where the landscape features were more favourable to each of these species (i.e., in the plateau for T. floralis and in the mountains for P. borbonicus). Landscape provided a comparably much stronger effect than farming practices, and the percentage of variation explained by landscape, as a standalone factor, was approximately five times higher than for farming practices. Spatial heterogeneity and seasonality also provided a large and significant proportion of random variability. Our results stress how verifying a generally accepted paradigm of sustainable agriculture, “agroecology promotes abundance and diversity of beneficial insects”, might require careful consideration, as, under field conditions, the impact of sustainable farming practices on insect communities might be embedded within complex, multi-layered ecological interactions.